Pelatihan Pembuatan Balsem dan Krim Gosok pada Kelompok 'Aisyiyah IV Blawong - Trilestari (DHARMA BAKTI, 2021)
The use of liniment in effort to self medicate various minor ailments in the Blawong Community is very frequent. Almost all families have a supply of these drugs. This training was conducted in order to introduce how to make rubbing balsem and cream to the group of ‘Aisyiyah IV Blawong Trimulyo Jetis bantul. The stages of the activity were carried out by surveying and coordinating with ‘Aisyiyah group administrators and campus managers. Continue to prepare tools, materials, training materials and administrative equipment. The activity was held on Saturday, April 27, 2019 at 13.00 and was attended by 30 people. With this training, the women of the ‘Aisyiyah IV Blawong Trimulyo Jetis Bantul have learned how to make rubbing balsam and cream. With this training, it is hoped that the self medicated ability of the women of the group ‘Aisyiyah IV Blawong Trimulyo Jetis Bantul in overcoming the symptoms of minor illnesses such us fever, dizziness, aches, nasal congestion, insect bites and others. This balsam and cream making training also had economic value.